Digital Marketing Strategy in the Industry 5.0 Era - Vera Maria; Nabylla Zahra; Safina Prabowo (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
In the era of Industry 5.0, when technology and innovation are advancing at a very rapid pace, digital marketing strategies are becoming increasingly important for business success. This study aims to analyze various digital marketing strategies that are effective in the Industry 5.0 age and to identify the key factors that affect their implementation. This study suggests that in order for businesses to remain competitive in the Industrial 5.0 era, they must quickly adapt to the rapid advancements in technology and adopt more innovative and collaborative work practices in their digital marketing strategies.